Gambaran Penjualan dan Investasi Obat Bermerek Apotek “X” Kelurahan Kampung Satu Kota Tarakan Menggunakan Analisis ABC Periode Tahun 2022 - Yulianti Clarisa Febrilia; Syuhada Syuhada; Benazir Evita Rukaya (Journal Borneo, 2024)
Pharmacies as facilities that are authorized to manage the inventory of pharmaceutical supplies need to anticipate inventory problems, both over stock and out stock. Pareto ABC analysis is one solution to overcome planning and procurement problems which tend to be ineffective and inefficient. This research aims to determine the sales and investment value of branded drugs at one of the private pharmacies in Tarakan City. This research is a retrospective study using the Pareto ABC analysis method on branded drug sales data in 2022. Based on sales data, 761 types of branded drugs were analyzed. The data is then grouped based on sales value. As for the results obtained, group A consisted of 189 types of drugs, or the equivalent of 24.84% of the total types of drugs, with a sales value of 17,986 items and an investment value of IDR. 209,828,250. Meanwhile, group B consists of 205 types of drugs, or the equivalent of 26.94% of the total types of drugs, with a sales value of 5,155 items and an investment value of IDR. 60,177,500. Meanwhile, for group C there are 367 types of drugs, or 48.23% of all types of drugs, with a sales value of 2,573 items and a total investment value of IDR. 30,107,100. This indicates that inventory monitoring and management can be adjusted to the characteristics and investment size of each drug category.